THE BAN OF ASSOCIATION OF CROATIAN THEATRE VOLUNTEERS BY COMMUNIST AUTHORITIES IN CROATIA (1945 – 1947) (Review of Croatian History, 2019)
The article describes the ban of Association of Croatian Theatre Volunteers in Zagreb [Matica hrvatskih kazališnih dobrovoljaca, Zagreb], umbrella theatrical-volunteer organization in Croatia since the mid-1920s until Second World War. It was active in the country and abroad on popularisation of the art of drama, creation of  the folk repertoire, as well as on bringing together acting societies, clubs and choirs. When the war ended, the Association applied for permission to restore its activities, but only in the Zagreb area. Its activities would be mainly related to education of actors – theatre volunteers and improving of theatre literature. The procedure of banning lasted from the autumn of 1945 until 5 February 1947, when the Government of the People's Republic of Croatia (PRC) [Vlada Narodne Republike Hrvatske] confirmed the ban order previously adopted by Ministry of Interior of the PRC [Ministarstvo unutrašnjih poslova Narodne Republike Hrvatske]. Also, its whole property was confiscated in favour of the State. The article also draws attention to the engagement in that ban case, showed by Aleksandar Freudenreich, a prominent architect and theater worker, as well as secretary of the Association in whole period since its founding.  The ban case was analyzed in a broader context of creating a new socialist culture, in accordance with the revolutionary ideology of the new communist government.